1981
DOI: 10.1002/bit.260230309
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of uranium and thorium

Abstract: SummarySelected samples of waste microbial biomass originating from various industrial fermentation processes and biological treatment plants have been screened for biosorbent properties in conjunction with uranium and thorium in aqueous solutions. Biosorption isotherms have been used for the evaluation of biosorptive uptake capacity of the biomass which was also compared to an activated carbon and the ion exchange resin currently used in uranium production processes. Determined uranium and thorium biosorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
137
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(155 citation statements)
references
References 4 publications
16
137
0
2
Order By: Relevance
“…Studies 31,32 have reported that increase in fungal biomass dose generally increases the metal uptake rate due to increase in the number of binding sites. Hence increase in the biosorbent surface area, followed by slower metal deposition indicate a secondary metal-binding mechanism 33 . Figure 10 shows optimal metal concentration of 150 mg/l for maximum removal of copper and zinc, i.e.…”
mentioning
confidence: 99%
“…Studies 31,32 have reported that increase in fungal biomass dose generally increases the metal uptake rate due to increase in the number of binding sites. Hence increase in the biosorbent surface area, followed by slower metal deposition indicate a secondary metal-binding mechanism 33 . Figure 10 shows optimal metal concentration of 150 mg/l for maximum removal of copper and zinc, i.e.…”
mentioning
confidence: 99%
“…The tests are usually performed at approximately 25-30ºC. However, Tsezos and Volesky, (1987); Kuyucak and Volesky (1989) and Aksu and Kutsal *Corresponding author (1991) reported a slight increase in cation uptake by seaweed in the range of 4 to 55ºC.…”
mentioning
confidence: 99%
“…Each of the mixture was placed on a magnetic stirrer and agitated for a period of 1 hour to extract soluble organic compounds. The solid was filtered off and the dissolved organic carbon content determined [75][76][77][78][79][80][81][82].…”
Section: Determination Of Secondary Pollution In the Treated Watermentioning
confidence: 99%